2011
DOI: 10.1128/aem.05271-11
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Glyphosate Resistance through Concurrent Mutations in Three Amino Acids of the Ochrobactrum 5-Enopyruvylshikimate-3-Phosphate Synthase

Abstract: A mutant of 5-enopyruvylshikimate-3-phosphate synthase from Ochrobactrum anthropi was identified after four rounds of DNA shuffling and screening. Its ability to restore the growth of the mutant ER2799 cell on an M9 minimal medium containing 300 mM glyphosate led to its identification. The mutant had mutations in seven amino acids: E145G, N163H, N267S, P318R, M377V, M425T, and P438L. Among these mutations, N267S, P318R, and M425T have never been previously reported as important residues for glyphosate resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…A number of mechanisms have been identified as being responsible for glyphosate resistance in several weed species; alterations of the target site via a mutation in the EPSPS gene so that it is no longer inhibited by glyphosate or overexpression of EPSPS in Eleusine indica, Lolium rigidum and Orchobactrum anthropi (Baerson et al 2002;Kaundun et al 2011;Powles and Yu 2010;Tian et al 2011); reduced In many cases, glyphosate resistance is the result of the combined action of several or all of some previously described mechanisms as reviewed by Powles and Yu (2010), Shaner et al (2012) and recently by Sammons and Gaines (2014). The previous mechanisms are documented on a wide range of weed species representing several genus and families.…”
Section: Discussionmentioning
confidence: 99%
“…A number of mechanisms have been identified as being responsible for glyphosate resistance in several weed species; alterations of the target site via a mutation in the EPSPS gene so that it is no longer inhibited by glyphosate or overexpression of EPSPS in Eleusine indica, Lolium rigidum and Orchobactrum anthropi (Baerson et al 2002;Kaundun et al 2011;Powles and Yu 2010;Tian et al 2011); reduced In many cases, glyphosate resistance is the result of the combined action of several or all of some previously described mechanisms as reviewed by Powles and Yu (2010), Shaner et al (2012) and recently by Sammons and Gaines (2014). The previous mechanisms are documented on a wide range of weed species representing several genus and families.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of directed evolution through DNA shuffling, which targets the glyphosate-resistance of EPSPS, Tian et al (2011) obtained mutant EPSPS with increased glyphosate resistance and enzyme activity (Tian et al 2011). Their finding suggested that continued glyphosate selection pressure on mutant DNA library constructed by DNA shuffling is an ideal condition in which to achieve mutant EPSPS that reduce glyphosate sensitivity while still maintaining catalytic efficiency in nature.…”
Section: Dna Shuffling and Sequencingmentioning
confidence: 96%
“…For instance, the residues of N267S, P318R and M425T of EPSPS from Ochrobactrum anthropi and the residues of T101A and A187T of the EPSPS from Malus domestica have been recently reported as important residues for glyphosate resistance. The two mutants have also been used to generate glyphosate-resistant plants (Tian et al 2011(Tian et al , 2013. Therefore, it suggested that DNA shuffling is an effective strategy to produce the mutated EPSPS with improved glyphosate-resistance in bacterial and plants.…”
Section: Introductionmentioning
confidence: 99%
“…According to the three-dimensional structure, many active sites of EPSP synthase have been identified and studied. For example, mutations of Gly-96 to Ala in the EPSP synthase of E. coli (Class I) (Padgette et al 1988;Eschenburg et al 2002), Pro-101-Leu in EPSP synthase from S. aureus (class II) (Priestman et al 2005), and Pro-318-Arg in EPSP synthase from O. anthropi (class II) (Tian et al 2011) can result in significant changes in glyphosate tolerance. The equivalent residues in AroA S. fredii are Gly-100, Leu-105 and Glu-318, respectively ( Figure S1).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, this altered amino acid may play an important role in the glyphosate resistance of AroA S. fredii . Position 318 lies at the upper surface of the lower hemisphere of the enzyme, any mutation in this ''emerging active site'' of inner cleft may indirectly cause conformational changes in the hydrogen bonding networks, resulting in positional shifts in adjacent and nearby residues around S3P/PEP, then affects the glyphosate tolerance (Tian et al 2011;Stauffer et al 2001).As for the proteins AroA S. fredii and AroA O. anthropi , the important residues for S3P binding and PEP binding and the domains for glyphosate tolerance are found to be conservative. But sequencing alignments reveal a Glu at position 318 in AroA S. fredii instead of proline as is seen with AroA O. anthropi .…”
Section: Discussionmentioning
confidence: 99%